Congenital adrenal hyperplasia due to steroid 21-hydroxylase deficiency epidemiology, etiopathogenesis, clinical presentation, treatment – a systematic review - Babik, Adrianna; Kamińska, Kamila; Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga Anna; Klamka, Antoni; Kawalec, Paulina; Bronikowski, Kamil; Ryszkowski, Maksymilian; Fornal, Krystian (Quality in Sport, 2026)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders of the adrenal cortex caused by a deficiency of an enzyme involved in adrenal steroidogenesis. In the majority of cases (95%), this deficiency affects the enzyme 21-hydroxylase. A deficiency or complete absence of enzymes involved in steroidogenesis disrupts the steroidogenic pathways, resulting in increased synthesis of steroid hormone precursors, which leads to an excess of adrenal androgens and virilization in female patients. The aim of this study was to review the current literature on the epidemiology, etiopathogenesis, and clinical presentation of congenital adrenal hyperplasia due to 21-hydroxylase deficiency, as well as to discuss contemporary treatment methods for this condition. Congenital adrenal hyperplasia due to 21-hydroxylase deficiency is a complex disorder with a broad clinical spectrum, requiring a multidisciplinary diagnostic and therapeutic approach. The pathophysiology of the disease is based on cortisol and aldosterone deficiency combined with an excess of adrenal androgens, which results in different clinical presentations depending on the patient's age, sex, and the severity of the genetic variant. The implementation of universal newborn screening based on 17OHP measurement has significantly reduced mortality associated with adrenal crisis, particularly in boys, in whom the normal appearance of the external genitalia delayed diagnosis. Replacement therapy with hydrocortisone and fludrocortisone, although effective, does not fully replicate the physiological circadian rhythm of cortisol secretion and is associated with a risk of numerous long-term complications. Therapeutic prospects include CRF receptor antagonists, molecules inhibiting ACTH secretion, and gene therapy, although none of these approaches has yet entered routine clinical practice.